Assessment of the Inhibitory Effect of Rifampicin on Amyloid Formation of Hen Egg White Lysozyme: Thioflavin T Fluorescence Assay versus FTIR Difference Spectroscopy. (6th January 2014) - Ma, Gang; Zhang, Hong; Guo, Jianhua; Zeng, Xiaodan; Hu, Xiaoqian; Hao, Wenying
Abstract : The inhibitory effect of rifampicin on the amyloid formation of hen egg white lysozyme was assessed with both Thioflavin T (ThT) fluorescence assay and Fourier transform infrared (FTIR) difference spectroscopy. We reveal that ThT fluorescence assay gives a false positive result due to rifampicin interference, while FTIR difference spectroscopy provides a reliable assessment. With FTIR, we show that rifampicin only has marginally inhibitory effect. We then propose that FTIR difference spectroscopy can potentially be a convenient method for inhibitor screening in amyloid study.